GEOCHEMICAL FIELD STRUCTURES IN DEPOSITS OF THE NORTHEASTERN USSR - Grigorov S.A.; Kuklin A.A.; Kuklin A.P.; Karavayeva V.A.; Rozenblyum I.S. (My University, 1988)
The concept of geochemical field structure was developed in modeling of the geochemical fields of ore-bearing structures at various hierarchical levels, from ore shoots to ore zones. The structure-producing elements in a multicomponent geochemical field are geochemically uniform zones (GUZ) identified by classification and cluster analysis of geochemical data. The main property of structure of geochemical fields is the alternation of geochemically uniform zones of high and low concentrations of individual chemical elements, between which there is heat and mass transfer. The ensemble of alternating structures of geochemically uniform zones make up multilevel zonal, insular, or closed concentric structures whose focal planes or points indicate the starting and ending points of the back and forth development of hydrothermal systems. These ensembles or constructs are called the geochemical halo systems of ore bodies. All of the known gold-ore and tin-tungsten deposits of the northeastern USSR obey the model of the halo-system concentric structure with a core and at least three zone. The volume ratios of the zones are generally 1 : (5 to 10) : (10 to 40). These and other aspects of the subject are discussed.